Aplikasi Sewa Mobil Berbasis Web pada PT Indomobil Car Rental - Tri Pujadi (Bina Nusantara University, 2011)
Indomobil Car Rental (IndoRent) is a rental firm providing service to customer by provides vehicle and qualified drivers. Firm has extensive network by utilizes all network from Indomobil Group. Besides it also have care service network that exists at several big cities in Indonesia. Common service problems for customer is limitation of the number of drivers to service customer, particularly at the busy days where it is difficult for customers to do reservation and get information to rent a car. Company website does not provide rent price and car amount information. This application design is developed from a financial application system therefore making it easy for users to conduct activity or transactions and service that progressively increases. Method for modelling by use of Rational Rose, meanwhile design web application utilizes Macromedia Dreamweaver, and Macromedia Flash MX and Swishmax for its animation.This application utilizes PHP and MySQL. The website of Indomobil Rental Car is expected to be more dynamic and can pull more visitors its, so increases firm performance.